proof of concept that participation of rice farmers to contract farming increased their income by $140 per capita in Benin - CGIAR Research Program on Rice (2021)
A survey among contract farmers indicated that contract increases productivity by 473 kg per hectare or about 29 percent higher yields than the control (n=733 for contract farmers ; n=220 for control group). Households with farming contracts increased their market participation by selling 35% points more of their rice harvest, a 140 percent increase above farmers without contracts. This increased land size, higher productivity, and greater market participation resulted in treated households earning $140 more income per capita (+230%).